A Research-Based Approach to the President-Principal Model: Problems, Dynamics, and High Performance Through Administrative Alignment - James, John T. (Catholic Education: A Journal of Inquiry and Practice, 2009)
Many Catholic high schools have transitioned to a president-principal administrative structure. This article discusses the strengths and weaknesses of the model, revealing pertinent issues that must be addressed while operationalizing the model. Recent research supports some aspects of the model, but it is no panacea. Clear job descriptions, role expectations, and administrative alignment can help the model succeed.